2016
DOI: 10.24188/recia.v8.n0.2016.397
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la suplementación con zinc y selenio sobre la calidad seminal en cerdos

Abstract: El sistema de producción porcina en Colombia, ha tenido un gran crecimiento en los últimos años, gracias a la implementación de técnicas como la inseminación artificial, la cual permite realizar un mejoramiento genético incrementando la productividad. Sin embargo, el modelo de manejo de los reproductores y donantes de semen no es el adecuado, siendo mantenidos en confinamiento, alimentados con dietas que no suplen los requerimientos de micronutrientes (Zn y Se) alterando la calidad seminal. Por lo anterior, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The decrease in sperm motility can be due to inappropriate use of ATP ( 59 ) and/or damage to the membrane integrity induced by ROS ( 60 ). Some authors have shown that Se helps improve sperm motility as it acts as a cofactor for the antioxidant enzyme GPx ( 61 ), and antioxidants are the most important defense against oxidative stress in the cell ( 51 ). Other studies in avian species showed that fat-soluble vitamin supplementation improves semen quality and quantity, especially sperm viability and motility ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in sperm motility can be due to inappropriate use of ATP ( 59 ) and/or damage to the membrane integrity induced by ROS ( 60 ). Some authors have shown that Se helps improve sperm motility as it acts as a cofactor for the antioxidant enzyme GPx ( 61 ), and antioxidants are the most important defense against oxidative stress in the cell ( 51 ). Other studies in avian species showed that fat-soluble vitamin supplementation improves semen quality and quantity, especially sperm viability and motility ( 62 ).…”
Section: Discussionmentioning
confidence: 99%